Validity Analysis of the Science Learning Tools using OrDeP2E Models with Contextual Approaches to Improve Creative Thinking Skills of Junior High School Students (Jurnal Pendidikan Fisika, 2020)
The OrDeP2E learning model based on a contextual approach is a science learning activity based on a contextual approach that emphasizes the creative thinking process of junior high school students. The syntax of the OrDeP2E learning model stands for: 1) Problem definition, 2) Problem Orientation, 3) Hypothesis Submission, 4) Hypothesis Testing, and 5) Evaluation. This study aims to obtain the OrDeP2E model of natural science learning tools with a contextual approach that is appropriate for improving the creative thinking of junior high school students. This study refers to the development of the 4-D model. The results showed that the development of natural science learning tools are suitable to be applied in science learning with the following results: the syllabus got a score as many as 3,45 (valid), the implementation plan of learning got a score as many as 3,53 (valid), teaching material got a score as many as 3,50 (valid), student worksheets get a score as many as 3,63 (valid), creative thinking skills test get a score as many as 3,55 (valid).